Hypothyroidism being caused by chronic autoimmune inflammation of the thyroid gland - Szwajkosz, Katarzyna; Wawryniuk, Agnieszka; Sawicka, Katarzyna; Łuczyk, Robert; Tomaszewski, Andrzej (Journal of Education, Health and Sport, 2017)
Disorders of the endocrine system are extremely important problems in Poland and around the world. According to the data presented by the Central Statistical Office in Poland in 2006, 22 % of the population suffered from thyroid disorders. Hypothyroidism is usually caused by chronic autoimmune inflammation of the thyroid gland. It is one of the most common disorders of the thyroid concerning approximately 2% of the adult population. This disorder is related to higher risk of overweight and obesity due to decreased total body metabolism. Furthermore, it predisposes to dyslipidaemia thus increases the risk of cardiovascular disease.